Praktek Jual Beli pada Marketplace dalam Perspektif Etika Bisnis Islam - Hikmatus Sa’diyah; Anugrahi Putri Ziyadatin Ilmi; Ananta Delyana Mafikah; Rika Nur Amelia; Silvi Indah Nurvita Sari; Eny Latifah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research examines the implementation of Islamic business ethics in the practice of buying and selling in the marketplace. The background is the rapid growth of the marketplace as a digital innovation that facilitates buying and selling transactions, but still presents challenges such as dishonesty, unfairness, and non-transparency. This research uses a literature review-based qualitative method to explore the principles of Islamic business ethics such as tawhid, justice, responsibility, and honesty in the context of marketplaces. The findings show that the application of Islamic business ethics can create a more transparent, fair, and sustainable business ecosystem. Platforms such as Tokopedia, Shopee, and Bukalapak have adopted these principles through review, return, and product verification systems. The research results provide a practical contribution in building a digital marketplace that is aligned with sharia values, supports global economic sustainability, and increases consumer trust.